Cuidado de enfermagem em terapia intensiva cardiológica: hermenêutica do conceito fundamentada na fenomenologia heideggeriana - Silva, Lucia de Fatima da (2002)
This research, whose subject is the meaning of the concept of the nursing care, was developed with the intent to reveal the notion that is behind the speech of nurses, assistants and patients on the an intensive cardiologic therapy of a public hospital in Fortaleza, Brazil. The presupposition was that, for these professionals, the concept of the nursing care is filled with modes of proceeding that not always consider the patients' necessities, hopes and yearnings. To achieve this work's goals, a phenomenological study based on Martin Heidegger's comprehensive hermeneutics was carried out. The information was collected by means of interviews and proper observation of the process of attending upon patients, in the period of October, 2000 to July, 2001. All the ethical norms recommended for a research that involves human beings were taken into account. From the interviews, it soon became clear that the concept of the nurse's care is taken as the satisfaction of the circumstantial needs of the patients, a task implemented mainly by the execution of a few scientifically based technical procedures that are worthy to be applied while still showing a humanistic attitude. From this evidence, it was possible to interpret that the professionals, influenced by the historicity of Nursing and by today's world where the work of caring is imprisoned to a technical-scientific dimension, assume the rhetoric of a speech concerning a humanized care which very often does not agree with the reality. This situation separates the professionals from the yearnings revealed by the patients in that they want to be taken care of with an authentic solicitude. From the results of the study, it is hoped that the education of nursing as well as nurses' daily activities be reviewed so as to increase the value of the agreement between the nurses' task and the patients' expectations of not being dismissed of their condition as human beings. The study also contributes to the theoretical development of Nursing, as it attempts to reveal the original meaning of one of its most relevant concepts.